Analysis on genetic contribution of some traits*to seed yield in rapeseed by additive-dominance genetic method of mixed model. - Sabagbnia, N.; Dehghani, H.; Alizadeh, B.; Mohghaddam, M. (Plant Breeding and Seed Science, 2010)
A genetic model is developed with additive, dominance and genotype × environment interaction effects for the progeny from a diallel mating design. To uncover the genetic contributions of some traits of rapeseed to seed yield and find indicator traits for indirect selection, multivariable conditional analysis was conducted based on this method. Therefore, an experiment was conducted to estimate genetic parameters using a half diallel of nine international rapeseed cultivars. The 36 F1 hybrids, the parents and four additional cultivars were planted in the breeding nurseries in 2008 and 2009. Several traits including number of pods per plant (NPP), pod length (LP), height of the first pod (HFP), height of the first lateral branch (HFB), stem diameter (SD), days of flowering period (FP), days to physiological maturity (DPM) and seed yield were recorded. The genetic variance component (VD×Y) was significant for all the studied traits but the genetic variance component (VA) was significant for NPP, HFB, HFP, DPM and SY traits and the genetic variance component (VD) was significant for HFB, HFP, LP and FP traits. There was significant positive phenotypic correlation (rA) between seed yield with NPP and HFP and there was significant positive dominance × year interaction correlation (rD×Y) between seed yield with NPP and DPM while there was significant negative dominance × year interaction correlation (rD×Y) between seed yield with HFB, LP and FP. There were significantly positive additive effects of SY for two parents Orient and Talaye. Finally according to additive-dominance genetic model and conditional genetic effects, the genotypes Talaye proved good general combiner for seed yield improvement and crosses 4 × 8 (Orient × Talaye), 7 × 8 (Opera × Talaye) were found the best specific combiner for all the studied traits...